Experimental study of stress-strain behaviour of open-cell aluminium foam sandwich panel for automotive structural part - Ibrahim, Nur Asmawiyah; Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas; Endut, Nor Amalina; Asman, Asyfiq Hanif (Deer Hill Publications, 2017)
Because of high stiffness and strength to weight ratio, aluminium foam sandwich (AFS) has huge advantage in automotive industries in order to reduce the vehicle’s weight which consequently will reduce the fuel consumption. While reducing the weight, AFS must also maintain high strength and durability compared to other competitive materials used which perform same functionalities. AFS had been proved its suitability for industrial application by previous researchers such as in aerospace, automotive and architecture. However, there is still a gap need to be filled in order to expand the use of the AFS in another application. In this paper, the tensile strength of AFS panel made of from aluminium skin sheets and open-cell aluminium foam core with various thicknesses is investigated. To achieve the objectives of the research, experimental work has been conducted. Full factorial of two independent factors: core thickness with two levels and skin thickness with three levels. JMP software (version 11) has been used to analyse the data. Experimental work was done using universal testing machine. The stress-strain behaviour was analysed. The result shows that the effect of skin to core ratio is significant on the stress-strain behaviour.